2016
DOI: 10.18632/oncotarget.13158
|View full text |Cite
|
Sign up to set email alerts
|

Senescent stromal cell-induced divergence and therapeutic resistance in T cell acute lymphoblastic leukemia/lymphoma

Abstract: T cell Acute Lymphoblastic Leukemia/Lymphoma (T-ALL/LBL) is a precursor T cell leukemia/lymphoma that represents approximately 15% of all childhood and 25% of adult acute lymphoblastic leukemia. Although a high cure rate is observed in children, therapy resistance is often observed in adults and mechanisms leading to this resistance remain elusive. Utilizing public gene expression datasets, a fibrotic signature was detected in T-LBL but not T-ALL biopsies. Further, using a T-ALL cell line, CCRF-CEM (CEM) cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…To assess the binding of AD-114-6H to lung tissue associated CXCR4, IHC staining with AD-114-6H was initially optimized on spleen and liver tissue from immunocompromised SCID/bg mice that had been challenged with an intravenous injection of CXCR4-expressing human leukemic T cells, CCRF-CEM cells, ( 27 , 34 36 ) ( Figure S2 ) . AD-114 immunolabeled few cells in NDC lung explants (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the binding of AD-114-6H to lung tissue associated CXCR4, IHC staining with AD-114-6H was initially optimized on spleen and liver tissue from immunocompromised SCID/bg mice that had been challenged with an intravenous injection of CXCR4-expressing human leukemic T cells, CCRF-CEM cells, ( 27 , 34 36 ) ( Figure S2 ) . AD-114 immunolabeled few cells in NDC lung explants (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…SCID/Bg mice were intravenously administered with CCRF-CEM cells as previously described 36 . Mice were sacrificed 25–27 days after cellular administration and their spleens and livers were fixed, paraffin embedded, sectioned and stained with AD-114-6H or control i-body.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study that investigates the mechanisms of therapy resistance observed in T‐cell acute lymphoblastic leukemia/lymphoma (T‐ALL/LBL), a fibrotic signature was detected in cancer cells . The data indicated that senescent rather than proliferating stromal cells induced such a signature in malignant cells, partially due to the enhanced production of oxidative radicals and EVs containing miRNAs that target BRCA1 and the mismatch repair (MMR) pathway components .…”
Section: Therapeutic Resistance Can Be Conferred By Evs Of Stromal Cementioning
confidence: 99%
“…Acute lymphoblastic leukemia (ALL) is an aggressive neoplasia characterized by the uncontrolled proliferation of aberrant lymphocytes, and represents the most common childhood cancer [ 1 3 ]. Over years, several efforts have been made for the best treatment approach, such as combination of chemotherapy and radiotherapy [ 4 , 5 ]. These therapies, however, may impair the whole child health status and quality of life through different side effects which include osteopenia, muscle atrophy, cardiovascular and cardiopulmonary problems or metabolism alterations [ 6 9 ].…”
Section: Introductionmentioning
confidence: 99%